Importance of cone-beam computed tomography in dentistry: An update - Shruthi Hegde; Vidya Ajila; Jasmine Shanti Kamath; Subhas Babu; Devika S Pillai; S Mithula Nair (SRM Journal of Research in Dental Sciences, 2018)
In this era of advanced technology, cone-beam computed tomography (CBCT) has gained popularity in the field of oral radiology due to its advantages over conventional radiography. The use of CBCT is profoundly increasing for diagnosis and treatment planning in different specialties of dentistry. The incorporation of cone-beam technology into clinical practice is taking place because of the progress in image acquisition and three-dimensional (3D) imaging. The equipment design is easier to use, image distortion is minimal, and the images are compatible with other planning and simulation software. The 3D imaging has made the complex craniofacial structures more accessible for examination. Early and accurate diagnosis of deep-seated lesions is possible. CBCT provides a high-spatial resolution of bone and teeth which allows accurate understanding of the relationship of the adjacent structures. CBCT has helped in detecting a variety of cysts, tumors, infections, developmental anomalies, and traumatic injuries involving the maxillofacial structures. It has been used extensively for evaluating dental and osseous disease in the jaws. This paper reviews current advances in CBCT and their uses in dentistry.